TINJAUAN YURIDIS TINDAK PIDANA PEMBANTUAN PENCURIAN DENGAN PEMBERATAN (PUTUSAN NOMOR 241/PID.B/2021/PN SBG) - Ronaldo; Aprima Suar (Reformasi Hukum Trisakti, 2022)
There are circumstances or a chronology of cases that are essentially this is a qualification of the elements of Article 363 Paragraph 1, 3 in conjunction with Article 56 of the Criminal Code that regulates the crime of assisting theft with weighting. As a defendant named Ranto Silaban, it has been decided and declared legally and convincingly proven guilty of committing the crime of collection in Article 480 1st of the Criminal Code. Problem statement: In the case study of Decision Number 241/Pid.B/2021/PN Sbg, is there a distinction between stealing by weighting and theft by receiving? Also, how are criminal penalties applied in this instance? The study is normative, descriptive-analytical, employs secondary data sources, qualitatively analyses, and applies the deductive technique to generate conclusions. The difference between stealing and weighting is defined in Article 363 Paragraph 1. Third of the Criminal Code, whereas collection is defined in Article 480. First of the Criminal Code, according to research findings, discussion, and conclusion. The penalty for violating Article 480 1 of the Criminal Code, which deals with receiving the strongest threat, is four years in prison. In this case, defendant Ranto helped commit theft with weighting in order to profit.